Base line data, diagnostic doses, and field monitoring of resistance to several insecticides in adult and immature populations of Trialeurodes vaporariorum (Homoptera: Aleyrodidae) in the Cauca Valley, Colombia - RODRÍGUEZ, ISAURA; MORALES, HÉCTOR; CARDONA-M., CÉSAR (Revista Colombiana de Entomología, 2003)
As a continuation to the work on insecticide resistance in whitefly populations in Colombia and Ecuador, line base data, LC50 and LC90 values, and diagnostic doses for imidacloprid, monocrotophos, carbofuran, carbosulfan, bifenthrin and lambdacyhalothrin were calculated. Adults of a susceptible variety of Trialeurodes vaporariorum maintained at CIAT since 1991 were used. Disks of the treated foliage were placed on agar inside petri dishes. All other insecticides were evaluated using glass vials coated with technical grade insecticides. Diagnostic doses for adults were 300 µg/vial (monocrotophos), 5 µg/vial (carbofuran), 100 µg/vial (carbosulfan), 5 µg/vial (bifenthrin), 500 µg/vial (lamdacyhalotrin), and 40 ppm (imidacloprid). Base line data, LC50 and LC90 values, and diagnostic doses were also established for first instar nymphs using the leaf-dip methodology with commercial dosages of diafenthiuron, buprofezin and imidacloprid. Diagnostic doses for nymphs were 300 ppm (diafenthiuron), 16 ppm (buprofezin) and 300 ppm (imidacloprid). The above mentioned diagnostic doses were used to monitor resistance to insecticides in adults and nymphs of T. vaporariorum variety in areas of the Cauca Valley, where excessive use of insecticides occurs. Adult populations showed high levels of resistance to organophosphates, intermediate resistance to pyrethroids, and susceptibility to carbamates and imidacloprid. No resistance to insect growth regulators and imidacloprid was detected among the nymph populations sampled.